Histone-modifying enzymes as drivers and therapeutic targets in androgen-resistant prostate cancer - Purohit, Tanaya A.; Bahr, Kayla; Yang, Bing; Schultz, Zachery; Lewis, Peter W.; Denu, John M.; Jarrard, David F. (Frontiers in Endocrinology, 2026)
Androgen deprivation therapy (ADT) remains the cornerstone of treatment for advanced, hormone-sensitive prostate cancer (HSPC), but responses are transient, and most patients ultimately develop castration-resistant prostate cancer (CRPC), a largely incurable stage of disease. The mechanisms driving resistance are not yet fully understood. Recent data suggest epigenetic dysregulation driven by alterations in chromatin remodelers and histone-modifying enzymes (HMEs) contributes significantly to prostate cancer (PC) progression and resistance to androgen-directed therapies. HMEs control chromatin structure and transcriptional programs, and their altered activity contributes to androgen resistance and tumor progression. HME inhibitors offer promising therapeutic potential, yet their effects are highly context-dependent, emphasizing the importance of biomarker-guided precision strategies and rational combination therapies. This review highlights the contribution of histone PTMs and HMEs to CRPC progression and discusses their potential as novel strategies to improve clinical outcomes.